The reception of Chaucer's shorter poems, 1400-1450 : female audiences, English manuscripts, French contexts - Doyle, Kara A. (Chaucer studies, 2021)
First full-length study of what the manuscript contexts can reveal about early reactions to Chaucer, and in particular his treatment of women.